PENGARUH PERSEPSI RISIKO, EKSPEKTASI RETURN, BEHAVIORAL MOTIVATION DAN KEMAJUAN TEKNOLOGI TERHADAP KEPUTUSAN INVESTASI DI PEER TO PEER LENDING SYARIAH - Yunita Alnanda Sarawatari; Asyari Hasan; Iva Laili (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2021)
This study aims to determine the effect of perceived risk, xpected returns, behavioral motivation and technological progress on investment decisions in Islamic peer to peer lending. The research method used is quantitative research methods with primary data obtained from questionnaire data measured using a likert scale. Data processing in this study using multiple linear regression analysis through SPSS software. The results showed that the variables of risk perception and behavioral motivation had a significant effect on investment decisions in Islamic peer to peer lending, while the variables of return expectations and technological progress had no effect on investment decisions in Islamic peer to peer lending. This research is useful for financiers and Islamic peer to peer lending companies in particular to be able to improve the company's performance in order to achieve the company's goals.